Smartcom: uma arquitetura inteligente de gerenciamento de consumo de energia para smart home - OLIVEIRA, Edvar da Luz (Universidade Federal do Pará, 2018)
With advances in information technology for a variety of areas, such as health and wellness, Smart Home based solutions using Internet of Things (IoT) technologies are gaining in popularity, including energy-saving alternatives based on Home Energy Management Systems (HEMS). This thesis defines an innovative architecture, called SmartCoM, which is implemented to monitor and manage residences using IoT technologies. Such a strategy involves defining the parameters that can affect the interoperability between measurement, management and the layers of data communication, which are the resources necessary for the hardware devices to perform the intended monitoring and measurement. In addition, an interface is defined by a middleware layer to integrate the management of external installations and the visualization of data through cloud services. The SmartCoM architecture is defined end-to-end in detail from the consumer's point of view and optimization strategies are employed for both the end customer and the utility. In order to evaluate the proposed architecture, a case study was elaborated, from which the viability of developing solutions for Smart Home according to the requirements described in SmartCoM is observed.